PAYROLL MODEL FOR ACADEMIC STAFF: A REAL OPTION IN A PRIVATE CAMPUS - Nunuh Nunuh; Arvina Wulandari (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2021)
The purpose of this study is to describe and provide input to the outside world that real thoughts are needed for educational staff in an institution that works. So far, educational staff in a campus institution differ in their salary, as an illustration that there is a campus that provides salaries to education staff in a large range with the educational standards of undergraduate graduates according to the needs of the positions on campus. The method used is to obtain case data in reality received by education personnel who work in campus institutions. The results of the study require good follow-up thinking using quantitative methods by looking for other variables that influence each other and qualitative methods that provide good results from informants, finished data, or comparing.